Purpose in life and lung function: an individual-participant meta-analysis of six cohort studies - Angelina R. Sutin; Yannick Stephan; Martina Luchetti; Justin Brown; Tiia Kekäläinen; André Hajek; Brice Canada; Sébastien Kuss; Antonio Terracciano (Respiratory Research)
Abstract Background Purpose in life is a psychological resource associated with better health outcomes across adulthood. It is unknown whether it is related to lung function, a key marker of health and longevity. We evaluate the replicability and generalizability of the cross-sectional association between purpose in life and lung function and whether purpose in life is associated with lower risk of developing poor lung function over time. Methods Participants were from six cohort studies with public data: Health and Retirement Study, Midlife in the United States study, Wisconsin Longitudinal Study, National Health and Aging Trends Study, English Longitudinal Study of Ageing, and Survey of Health, Ageing and Retirement in Europe (total N = 85,190). Participants reported on their purpose in life, and staff measured their peak expiratory flow with either a peak flow meter or a spirometer. Four cohorts (N = 11,595) had longitudinal assessments of lung function over up to 12 years. Linear regression was used to test the cross-sectional association between purpose and continuous lung function. Cox regression was used to test the association between purpose and risk of developing predicted lung function < 80% over time, a dichotomous outcome that categorized lung function into performance less than 80% of predicted function (= 1) and at least 80% of predicted function (= 0). Results In each cohort and aggregated in a random-effects meta-analysis, higher purpose in life was associated with better peak expiratory flow (meta-analytic effect = 0.07, p <.001). The association was generally similar across sociodemographic groups (e.g., age, sex). Every standard deviation higher purpose in life was associated with a 10% reduced risk of developing poor lung function over time (meta-analytic hazard ratio = 0.91, 95% confidence interval = 0.88, 0.94, p <.001). These associations were attenuated but remained significant accounting for behavioral and clinical risk factors. Conclusions Purpose in life is associated with healthier lung function, with evidence of replicability and generalizability, and with lower risk of developing poor lung function over time. Lung function may be one mechanism between purpose in life and healthier outcomes in older adulthood. Clinical trial number Not applicable.